2021
DOI: 10.1002/acn3.51385
|View full text |Cite
|
Sign up to set email alerts
|

Delta power robustly predicts cognitive function in Angelman syndrome

Abstract: Objective: Angelman syndrome (AS) is a severe neurodevelopmental disorder caused by loss of function of the maternally inherited UBE3A gene in neurons. Promising disease-modifying treatments to reinstate UBE3A expression are under development and an early measure of treatment response is critical to their deployment in clinical trials. Increased delta power in EEG recordings, reflecting abnormal neuronal synchrony, occurs in AS across species and correlates with genotype. Whether delta power provides a reliabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 58 publications
(125 reference statements)
4
29
0
Order By: Relevance
“…One potential explanation as to why we observed effects on EEG power spectral density (PSD) but no changes in behavioral performance is that the increase in delta power may not have substantial behavioral significance. However, we find this explanation unlikely in light of recent evidence from our laboratory illustrating reductions delta power with concomitant behavioral improvements [ 74 ] and a new report in humans with Angelman Syndrome [ 70 ]. A more likely explanation for the present data is that the IGF-2-induced delta power reduction was sub-threshold for behavioral change.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…One potential explanation as to why we observed effects on EEG power spectral density (PSD) but no changes in behavioral performance is that the increase in delta power may not have substantial behavioral significance. However, we find this explanation unlikely in light of recent evidence from our laboratory illustrating reductions delta power with concomitant behavioral improvements [ 74 ] and a new report in humans with Angelman Syndrome [ 70 ]. A more likely explanation for the present data is that the IGF-2-induced delta power reduction was sub-threshold for behavioral change.…”
Section: Discussionmentioning
confidence: 60%
“…Novel data uncovered by this work illustrated that acute systemic administration of IGF-2 reduced delta spectral power in EEG, a theorized biomarker in AS. This was a very promising initial finding, considering newly published data linking delta power to improvements in the Bayley Cognitive Assessment [ 70 ], prompting the prediction that an effect of IGF-2 on EEG would translate to behavioral improvements. However, disappointingly, the overwhelming majority of metrics for motor abilities, coordination, and learning and memory were unaffected and IGF-2 did not improve social communication, seizure threshold, or cognition.…”
Section: Discussionmentioning
confidence: 89%
“…We note that delta rhythms are abnormal during wake and sleep in AS. 11 , 14 We focused on wake data because it was more widely available and more reliably identified. The final data set included wake recordings of mean duration 37.4 min (range: 1 min–6.5 hrs).…”
Section: Methodsmentioning
confidence: 99%
“…Power spectra were calculated using the Chronux toolbox. 17 Following the procedure in Ostrowski et al , 14 we analyzed only occipital and parietal electrodes, O1, O2, P3, Pz, and P4 referenced to a group average across those electrodes. There, it was shown that delta power estimates from the uncleaned posterior electrodes provided the best predictor of cognitive function as these electrodes are free of muscle artifacts and provide the largest amount of data from which to estimate delta power.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation